Drylobed and hydrophilous ecobiomorphs of the Ternopol Plateau flora - V.G. Sobko; R.L. Javorivsky (Інтродукція Рослин, 2003)
The analysis of ground and hydrophilous ecobiomorphs of the Ternopol Plateau flora is carried out. Genetic connections of this flora with the Central Europe broadleaved forest flora, with the south steppe flora and with the rock Mediterranean one are examined.